MEMAHAMI TAFSIR, TA’WIL DAN TARJAMAH AL-QURAN - Maulana Maulana (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
This paper describes the meaning of knowledge in the fields of Tafsir, Ta'wil and Translation which is a necessary need, to enrich and at the same time explore the depth of meanings in the Qur'an, as well as to complement the treasures of knowledge in Islam. For this reason, the author will try to explore the meaning and understanding of tafseer, ta'wil and translation, along with the various approaches used by interpreters in interpreting the verses of the Qur'an, in order to get a glimmer of information from various viewpoints. The ability of each individual Muslim to understand the text of the Qur'an may be different, even though the object is the same verse. This happens because the interpreter views the Qur'an from a different perspective, different background, culture, intellectual level and maturity as well as the sharpness of the interpreter's spiritual instinct.